PEDAGOGICAL-THEORETICAL FOUNDATIONS OF THE USE OF MODERN INFORMATION TECHNOLOGIES IN THE CONDITIONS OF DIGITALIZATION OF THE EDUCATION SYSTEM (Modern American Journal of Biological and Environmental Sciences, 2026)
This article highlights the pedagogical and theoretical foundations of using modern information technologies in the process of digitalization of the education system. It analyzes the issues of developing a digital learning environment, the role of information technologies in the educational process, and the development of teachers’ digital competencies. Furthermore, the article reveals the possibilities of improving the quality of education, enhancing the teaching process, and developing innovative pedagogical activities through the use of modern information technologies.